2023
DOI: 10.3390/ijms24043826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanosecond Pulsed Currents on Directions of Cell Elongation and Migration through Time-Lapse Analysis

Abstract: It is generally known that cells elongate perpendicularly to an electric field and move in the direction of the field when an electric field is applied. We have shown that irradiation of plasma-simulated nanosecond pulsed currents elongates cells, but the direction of cell elongation and migration has not been elucidated. In this study, a new time-lapse observation device that can apply nanosecond pulsed currents to cells was constructed, and software to analyze cell migration was created to develop a device t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Considering that all three conditions (ELE, POS, and NEG) receive the same amount of electricity, it is interesting to see the differences between the electrical effects and the chemical effects. Regarding cell motility, previous our study has shown that the nanosecond pulsed current without plasma discharge do not result in a constant change in the direction of cell elongation or motility [32]. Based on the similar response to nanosecond pulsed currents with and without plasma discharges, motility with plasma discharges probably shows the same trend as without plasma discharges.…”
Section: Electrical Effects Of Plasmasupporting
confidence: 55%
“…Considering that all three conditions (ELE, POS, and NEG) receive the same amount of electricity, it is interesting to see the differences between the electrical effects and the chemical effects. Regarding cell motility, previous our study has shown that the nanosecond pulsed current without plasma discharge do not result in a constant change in the direction of cell elongation or motility [32]. Based on the similar response to nanosecond pulsed currents with and without plasma discharges, motility with plasma discharges probably shows the same trend as without plasma discharges.…”
Section: Electrical Effects Of Plasmasupporting
confidence: 55%
“…Generally human or animal cells elongate perpendicularly to the electric field and move in the direction of the electric field. Recently, Tada et al, showed that even plasmabased nanosecond pulsed current elongates cells, however, the direction of the movement and elongation was not defined [2]. In this research article, they used observed cell physiological behaviors after applying plasma stimulated pulse current.…”
Section: Plasma-induced Cell Motility and Wound Healingmentioning
confidence: 98%
“…Recently, Chang et al . and his colleagues constructed the system to evaluate the effect of plasma-induced nanosecond pulsed current and chemical factors on human HT-1080 cells activities and observed a significant increase in cell migration along with altered cell morphology 19 – 22 . Mendis et al .…”
Section: Introductionmentioning
confidence: 99%